O efeito da relação entre a motivação e o engajamento no desempenho do indivíduo da equipe de projetos em regime de trabalho presencial, híbrido e work from home - Mota, Celso Danilo da (2023)
With the emergence of the COVID-19 pandemic, many companies were forced to adopt the "work from home" arrangement, also known as remote work. This new work model led to significant changes in the behaviors and practices of individuals in project teams, which motivated the development of this research. Motivation and engagement are factors that can drive individual performance in project teams. Motivation can be understood as a set of reasons that lead a person or group to act in a specific way, involving the satisfaction of needs, autonomy, competence, and social relationships. This motivation can be influenced by various factors, such as the importance of the activity to the individual, rewards, or avoiding punishments, and personal interests. On the other hand, engagement is characterized by positive emotions, enthusiasm, and passion for work. These aspects are related to vigor, dedication, and absorption in work, potentially leading to greater emotional regulation and good mental health, translating into higher productivity, effectiveness, and efficiency in project tasks. Based on this context, the objective of this study is to analyze the effect of amotivation regulation and intrinsic motivation regulation on engagement and, consequently, analyze how engagement influences the performance of individuals in project teams. Then, an exploratory model survey is conducted in work regimes, including on-site, hybrid, and work from home, with the aim of exploring the explanatory capacity of isolated relationships by arrangement. To achieve this goal, this research adopts as a scientific procedure quantitative research method, using a survey for data collection through a Google Forms questionnaire. The scales were identified in the literature and rigorously selected to meet the research objectives. The analysis of the collected data was performed using structural equation modeling and multigroup analysis. This study builds a relationship between two relevant constructs in the project management field, motivation and engagement, and their impact on individual performance in project teams in the contexts of on-site, hybrid, and work from home arrangements. The findings of this quantitative research indicate that the proposed conceptual model was validated. However, when analyzing the arrangements separately, the model demonstrates average explanatory power for individual performance in project team on-site and hybrid arrangements, and low explanatory power for work from home, indicating a lack of variables to increase explanatory capacity. Thus, the results of this research can contribute to advancing knowledge in the field, providing insights for project managers to address team management challenges. It is expected that the results of this study can also provide valuable insights for companies and project managers seeking to optimize the performance of their teams in a remote work environment. Regarding theoretical contributions, the results obtained will advance discussions on the constructs of motivation, engagement, individual performance, and work arrangements, especially work from home. This research aligns with research line 2, "Project Management," linked to the Postgraduate Program in Project Management – PPGP UNINOVE. This dissertation is also aligned with other research by its advisor linked to the project-axis "Agile and Hybrid Projects."